Nutrient transporter pattern in CD56dim NK cells: CD16 (FcγRIIIA)-dependent modulation and association with memory NK cell functional profile - De Federicis, Davide; Capuano, Cristina; Ciuti, Daniel; Molfetta, Rosa; Galandrini, Ricciarda; Palmieri, Gabriella (Frontiers in Immunology, 2024)
BackgroundHuman memory NK cells represent a heterogeneous CD56dim population that expands and persists in human cytomegalovirus (HCMV)-seropositive healthy individuals. They are characterized by the preferential, not fully overlapping, expression of NKG2C (activating receptor for HLA-E) and CD57 maturation marker, and by the lack of FcεRIγ adaptor chain. Hyperresponsiveness to Fcγ receptor IIIA (CD16) engagement represents the distinctive functional signature of memory NK cells. Although CD16 engagement was shown to acutely enhance glycolytic and oxidative pathways, its capability to induce a persisting metabolic reprogramming of human NK cells is poorly understood yet.ResultsHere, we describe the peculiar nutrient transporter expression pattern of FcεRIγ- memory NK cells, characterized by higher levels of CD98 neutral amino acid antiporter and CD71 transferrin receptor, and lower expression of GLUT1 glucose transporter, with respect to FcεRIγ+ conventional NK cells. Although CD16 engagement acutely enhances glycolytic and oxidative pathways, its capability to induce a persisting metabolic reprogramming of human NK cells is poorly understood yet. Our results firstly show that sustained CD16 engagement by contact with IgG-opsonized target cells induces the mTORC1-dependent upregulation of CD98 and CD71 nutrient receptors on CD56dim NK cells, in a transporter-specific fashion, that is finely tuned by cell-dependent (grade of functional maturation, and memory or conventional lineage) and stimulus-dependent (time length and cooperation with cytokines) factors. We also demonstrate that CD98 antiporter function is required for CD16-dependent IFN-γ production, and that enhanced CD98-mediated neutral amino acid uptake associates with heightened memory NK cell functional response.ConclusionCollectively, our work documents that CD16 engagement leads to a metabolic rewiring of human NK cells and suggests that a distinct nutrient transporter expression pattern may contribute to memory NK cell peculiar functional features.